(untitled) (The Pakistan Development Review, 1980)
This paper surveys the problems encountered and solutions adopted in incorporating demographic phenomena in the main Bachue case studies undertaken to date, namely the demo-economic models constructed for the Philippines, Kenya, Brazil and Yugoslavia. Eight issues are treated: population accounting and lag structure; fertility; mortality; migration; nuptiality; household formation; schooling; and labour force paxticipation. In each case there is a discussion of model structure, dependent and ’explanatory variables, and empirical strategy. Summary tables compare the approaches of the different models. Although the objective is not to identify the best solution - it is noted that the specifics of every country situation rule this out - some suggestions about more promising approaches are made with respect to choice of variables to include, and the estimation of behavioural models.